Discovery and characterization of a positive allosteric modulator of transient receptor potential canonical 6 (TRPC6) channels. (March 2019) - Häfner, S.; Urban, N.; Schaefer, M.
Graphical abstract: Highlights: Compound screening on the canonical transient receptor potential channel 6 (TRPC6). Characterisation of a TRPC6-selective positive allosteric modulator C20. C20 increases Ca 2+ influx into platelets and augments platelet aggregation. Abstract: The non-selective second messenger-gated cation channel TRPC6 (transient receptor potential canonical 6) is activated by diacylglycerols (DAG) in a PKC-independent manner and plays important roles in a variety of physiological processes and diseases. In order to facilitate novel therapies, the development of potent inhibitors as well as channel-activating agents is of great interest. The screening of a chemical library, comprising about 17, 000 small molecule compounds, revealed an agent, which induced increases in intracellular Ca 2+ concentrations ([Ca 2+ ]i ) in a concentration-dependent manner ( EC50 = 2.37 ± 0.25 μM) in stably TRPC6-expressing HEK293 cells. This new compound (C20 ) selectively acts on TRPC6, unlike OAG (1-oleoyl-1-acetyl- sn -glycerol), which also activates PKC and does not discriminate between TRPC6 and the closely related channels TRPC3 and TRPC7. Further evaluation by Ca 2+ assays and electrophysiological studies revealed thatC20 rather operated as an enhancer of channel activation than as an activator by itself and led to the assumption that the compoundC20 is an allosteric modulator of TRPC6, enabling low basal concentrations of DAG to induce activation of the ion channel. Furthermore, C20 was tested in human platelets that express TRPC6. A combined activation of TRPC6 withC20 and OAG elicited a robust increase in [Ca 2+ ]i in human platelets. This potentiated channel activation was sensitive to TRPC6 channel blockers. To achieve sufficient amounts ofC20 for biological studies, we applied a one-pot synthesis strategy. With regard to studies in native systems, the sensitizing ability ofC20 can be a valuable pharmacological tool to selectively exaggerate TRPC6-dependent signals.